Epitaxial Growth of Intermetallic MnPt Films on Oxides and Large Exchange Bias. Issue 1 (5th November 2015) - Liu, Zhiqi; Biegalski, Michael D.; Hsu, Shang‐Lin; Shang, Shunli; Marker, Cassie; Liu, Jian; Li, Li; Fan, Lisha; Meyer, Tricia L.; Wong, Anthony T.; Nichols, John A.; Chen, Deyang; et al.
Abstract : High‐quality epitaxial growth of intermetallic MnPt films on oxides is achieved, with potential for multiferroic heterostructure applications. Antisite‐stabilized spin‐flipping induces ferromagnetism in MnPt films, although it is robustly antiferromagnetic in bulk. Moreover, highly ordered antiferromagnetic MnPt films exhibit superiorly large exchange coupling with a ferromagnetic layer.